Interleukin-17 and inflammatory bowel disease: a 2-sample Mendelian randomization study - Cai, Yangke; Jia, Xuan; Xu, Liyi; Chen, Hanwen; Xie, Siyuan; Cai, Jianting (Frontiers in Immunology, 2023)
Observational studies have discovered a contradictory phenomenon between interleukin-17 (IL-17) and inflammatory bowel disease (IBD). We performed a 2-sample univariable and multivariable mendelian randomization (MR) to determine which subtype of IL-17 is causally related to IBD and its subtypes, and used a series of sensitivity analysis to examine the reliability of the main MR assumptions. We found that IL-17B, IL-17E and IL-17RB were significantly associated with an increased risk of UC (IL-17B: OR: 1.26, 95% CI, 1.09-1.46, P < 0.01; IL-17E: OR: 1.17, 95% CI, 1.05-1.30, P < 0.01; IL-17RB: OR: 1.30, 95% CI, 1.20-1.40, P < 0.0001) while IL-17C and IL-17RC showed causal effects on the increased risk of CD (IL-17C: OR: 1.23, 95% CI, 1.21-1.26, P < 0.0001; IL-17RC: OR: 2.01, 95% CI, 1.07-3.75, P=0.03). The results of multivariable MR (MVMR) showed that the causal effects of IL-17B and IL-17E on UC were unilaterally dependent on IL-17RB, while the effects of IL-17C and IL-17RC on CD were interdependent. Our study provided new genetic evidence for the causal relationships between each subtype of IL-17 and IBD, promoting future mechanistic research in IBD.